An Econometric Analysis of Reservation Wages - Lancaster, Tony; Chesher, Andrew (Econometrica, 1983)
This paper describes an analysis of survey data on unemployed people who reported their asking wage and the wage they expected to earn. We show that if agents' behavior is described by the standard optimal job search model, one can use these data to deduce structural parameters rather than estimate them, and we report our deductions from two surveys^1 of British unemployed people.